Russian influence operations in the wars in Ukraine in 2014 and 2022: active measures and maskirovka - Staun, Jørgen; Eikeland, Patrick (Politica, 2023)
How does the Russian security and military elite think about influence operations? How have influence operations been used in practice in the two wars in Ukraine, in 2014 and 2022? We explore this by seeking to capture the Russian understanding of influence operations using the concepts “active measures” and “maskirovka”. As might be expected, Russia has used active measures and maskirovka in the wars against Ukraine. The greatest success was in 2014 when Ukraine and the West were virtually caught off guard and Crimea was captured almost without a fight. However, Russian influence operations have also been successful in 2022 invasion, primarily in misleading Ukraine about where the main attack was being launched. A misdirection that could have had fatal consequences for Ukraine.